2010
DOI: 10.1097/psy.0b013e3181e7fae8
|View full text |Cite
|
Sign up to set email alerts
|

Altered Human Neutrophil Function in Response to Acute Psychological Stress

Abstract: Objective: To examine the effects of an acute laboratory psychological stress task on neutrophil function, specifically phagocytosis of Escherichia coli and stimulated superoxide production in human neutrophils. There is mounting evidence that acute stress is associated with short-term increases in a number of immune indices. Methods:Participants were 40 (n = 20 females) university students (mean age, 25.9 ± 4.56 years). Blood samples to determine neutrophil function by flow cytometry were taken at the end of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 38 publications
3
14
0
1
Order By: Relevance
“…The neuroimmunoendocrine regulation of PrP C in neutrophils and its impact upon the cytotoxic potential of this cell may help explain previous observations that behavioral stress, which modifies both the risk and the course of various diseases (51)(52)(53)(54)(55) and strongly modulates the immune system (56 -58), also affects the cytotoxic functions of neutrophils (59). Notably, the cytotoxicity of neutrophils often swings toward the production of tissue damage (15,16).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The neuroimmunoendocrine regulation of PrP C in neutrophils and its impact upon the cytotoxic potential of this cell may help explain previous observations that behavioral stress, which modifies both the risk and the course of various diseases (51)(52)(53)(54)(55) and strongly modulates the immune system (56 -58), also affects the cytotoxic functions of neutrophils (59). Notably, the cytotoxicity of neutrophils often swings toward the production of tissue damage (15,16).…”
Section: Discussionmentioning
confidence: 73%
“…Notably, the cytotoxicity of neutrophils often swings toward the production of tissue damage (15,16). This warrants the examination of the hypothesis that the neuroimmunoendocrine regulation of PrP C may be involved in the deregulation of vascular permeability concurrent with inflammatory components of various pathological conditions (16,59,(61)(62)(63). Interestingly, disruption of endothelial tight junctions also follows exposure to hydrogen peroxide (64,65).…”
Section: Discussionmentioning
confidence: 99%
“…Kang et al (1997) found that examination stress increases superoxide production (1997). Acute psychological stress was reported to increase phagocytic ability and reduce superoxide production of neutrophils in humans (Khanfer et al, 2010), suggesting that the type of stress experienced has different effects on phagocytic abilities. Our current study did not distinguish between the contribution from neutrophil and monocyte/macrophage phagocytosis, which will be investigated later.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that stress modulates neutrophil and macrophage recruitment, chemokine gene expression and the adhesion molecule expression (Curry et al, 2010; Filep et al, 1997; Heasman et al, 2003; Mizobe et al, 1997; Viswanathan and Dhabhar, 2005; Zhang et al, 1998). In addition, stress was reported to alter neutrophil and macrophage microbicidal functions (Ehrchen et al, 2007; Khanfer et al, 2010; Palermo-Neto et al, 2003). Previous studies in a murine model of cutaneous healing showed that restraint stress increased susceptibility to opportunistic infection.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, acute stressors usually, with the exceptions of natural killer (NK) cell function (Cunnick et al 1988) and neutrophil superoxide production (Khanfer et al 2010(Khanfer et al , 2012, boost the immune system, particularly its innate component which is the one able to act quickly (Bosch et al 2003;Dhabhar and McEwen 1997;Sapolsky 1998). The majority of chronic stressors, on the other hand, are associated with global immunosuppression and have an impact on both innate and adaptive components of the immune system (Kiecolt- Glaser et al 1991a;Phillips et al 2006;Segerstrom and Miller 2004;Thaker et al 2006) to mention a few.…”
Section: Stress and The Immune Systemmentioning
confidence: 99%